RANCANG BANGUN SISTEM ADMINISTRASI KEPENDUDUKAN PADA KELURAHAN PENJALANG DENGAN MENGGUNAKAN METODE WEB ENGINEERING - mita, sas (STMIK Bina Nusantara Jaya Lubuk Linggau, 2019)
Population administration system in natural urban fence crossing urban villages still manually, still using a big book so that the population data search is still less effective. The purpose of this research is to design and build a population administration system in crossing urban villages by using PHP programming and MySQL Database. The methodology used is Web Engineering (web engineering). The results to be achieved are the availability of supporting applications in the urban village of Pagaralam that can be obtained without being bound by time and space. With this application in the weaving village it is expected to be able to help deliver information quickly and make it easy to get information about the weaving village.